A microscopic model for the dielectric function of Ge quantum wires - Alfaro, P.; Vazquez, R.; Lobota, I.; Ramos, A.E.; Cruz-Irisson, M. (Functional Materials, 2005)
Free-standing, infinitely long, and homogeneous quantum wires of square cross section are considered using the chessboard-like supercell model. The optical transition properties of Ge nanocrystals are studied by means of an sp³s* semiempirical tight-binding approximation. The calculations have been carried out for light polarized in the [100] direction, i.e., perpendicular to the wire alignment. Dependence of the imaginary part of the dielectric function on the quantum confinement is presented within two different schemes: intra-atomic and interatomic matrix elements, which are applied and compared. The principal results show that although the intra-atomic matrix elements are small in magni- tude, the interference between these terms and the interatomic matrix elements contrib- utes about 25 % of the total absorption. Thus, it appears that a quantitative treatment of nanostructures may not be possible (in general) without the inclusion of intra-atomic matrix elements. Вiльно стоячi однорiднi квантовi дроти квадратного перерiзу розглянуто з застосуванням шахової моделi комiрки надгратки. Оптичнi перехiднi властивостi нанокристалiв германiю дослiджено з використанням напiвемпiричного наближення сильного зв'язку sp³s*. Розрахунки виконано для свiтла, поляризованого в напрямi [100], тобто перпендикулярно простяганню дроту. Залежнiсть уявної частини дiелектричної функцiї вiд квантового обмеження представлено в рамках двох рiзних схем: внутрiшньоатомних та мiжатомних матричних елементiв, якi зiставлено один з другим. Основнi результати свiдчать, що, хоча внутрiшньоатомнi матричнi елементи мають незначну величину, внесок iнтерференцiї мiж цими термами та мiжатомними матричними елементами у загальне поглинання складає, приблизно 25 %. Таким чином, виявляється, що кiлькiсний розгляд наноструктур, загалом кажучи, є, неможливим без урахування внутрiшньоатомних матричних елементiв. Свободно-стоящие однородные квантовые проволоки квадратного поперечного сечения рассматриваются с применением шахматной модели ячейки сверхрешетки. Оптические переходные свойства нанокристаллов германия исследуются с помощью полуэмпирического приближения сильной связи sp³s*. Расчеты выполнены для света, поляризованного в направлении [100], т.е. перпендикулярно выстраивание проволоки. Зависимость мнимой части диэлектрической функции от квантового ограничения представлена в рамках двух различных схем: внутриатомных и межатомных матричных элементов, которые сопоставлены между собой. Основные результаты показывают, что, хотя внутриатомные матричные элементы имеют малую величину, вклад интерференции между этими термами и межатомными матричными элементами в суммарное поглощение составляет приблизительно 25 %. Таким образом, оказывается, что количественное рассмотрение наноструктур, в общем, невозможно без включения внутри-атомных матричных элементов.